Pengaruh Kinerja Keuangan, Tingkat Inflasi, Dan Kebijakan Dividen Terhadap Pertumbuhan Laba Perusahaan Dengan Harga Saham Sebagai Variabel Intervening Pada Perusahaan Perbankan Yang Terdaftar Di Bursa - Mutia Sahilna (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to examine the effect of Financial Performance, Inflation Rate, and Dividend Policy on Company Profit Growth, with Stock Price as an intervening variable in banking companies listed on the Indonesia Stock Exchange during the period 2020–2024. The research sample was determined using a total sampling method, resulting in 47 companies. The study used secondary data obtained from www.co.id, and the analysis was conducted using multiple regression analysis and path analysis with SPSS 25.Based on the results of this study, it was found that Financial Performance has a positive and significant effect on Stock Prices, Inflation Rate does not have a significant effect on Stock Prices, Dividend Policy has a positive and significant effect on Stock Prices, Financial Performance has a negative and significant effect on Profit Growth, Inflation Rate does not have a significant effect on Profit Growth, Dividend Policy has a positive and significant effect on Profit Growth, Stock Prices do not have a significant effect on Profit Growth, Stock Prices are able to mediate the relationship between Financial Performance and Profit Growth, Stock Prices are not able to mediate the relationship between Inflation Rate and Profit Growth, and Stock Prices are able to mediate the relationship between Dividend Policy and Profit Growth.